THE EFFECTIVENESS OF COLOR AND COMMENT ERROR MARKER IN PROVIDING UNFOCUSED-IMPLICIT CORRECTIVE FEEDBACK FOR UNDERGRADUATE STUDENTS' WRITING GRAMMAR - Purnama, Riza (2014)
Regardless being considered potentially ineffective by many (Lee, 2013), the provision of unfocused-implicit corrective feedback (CF) is considered an ideal way of addressing real-teaching problem (Ferris, 2010; Van Beuningen, 2010). This research was aimed at comparing the effectiveness of color and comment as error-marker in unfocused-implicit CF provision. The design used in this research was quasi-experimental design. Involving 64 participants, the data were collected through controlled observation and the observation of documents from10 randomly chosen participants. The findings had suggested significant difference between the two error-marking techniques where the use of comment was better than the use of color (sig 2-tailed = 0.011, p <.05). Such finding was further validated given that the use of comment was revealed to have facilitated better assistance towards revision of different type of errors (97.67%). In addition, it was also revealed that there were some circumstances where the provision of both strategies might have contributed to futile revisions. However, despite being outperformed, the use of color as error marker also resulted in noteworthy revising success which took up to 94.13%. Meskipundianggaptidakefektifolehsebagianbesar orang (Lee, 2013), pemberianumpanbaliksecaramenyeluruhdantersirat (unfocused-implicit corrective feedback) dianggapsebagaijalan yang ideal untukmenyikapiberbagaimasalahpengajaran yang nyataterjadi (Ferris, 2010; Van Beuningen, 2010).Penelitianiniditujukanuntukmembandingefektifitaspenggunaanwarnadankomentarsebagaipenandaletakkesalahandalampemberianumpanbalikmenyeluruhtersirat.Desain yang digunakandalampenelitianiniadalahquasi-experimental.Denganmelibatkan 64 partisipan, data didapatkanmelaluicontrolled ovservationsertapengamatanterhadapdokumendari 10 partisipan yang dipilihsecaraacak. Hasiltemuandaripenelitianinimenunjukkanperbedaan yang berartidiantarakeduacarapenandaankesalahandimanapenggunaankomentarmemberikanhasil yang lebihbaikdibandingkandenganpenggunaanwarna (sig 2-tailed = 0.011, p <.05). Temuaninilebihlanjuttervalidasiseiringtemuandimanapenggunaankomentarterbuktilebihefektifdalammendampingipartisipanmelakukanrevisibergaijeniskesalahan (97.67%).Selainitu, jugaditemukanbahwaterdapatbeberapakeadaandimanapemberiankeduastrategijugabisaberakhirdalamkegagalanrevisi.Namundemikian, terlepasdarinilai yang lebihkecil, penggunaanwarnasebagaipenandakesalahanjugamenghasilkankesuksesan proses revisi yang prosentasenyamencapai 94.13%.